Cyclooxygenase-2 inhibitor prevents radiation-enhanced infiltration of F98 glioma cells in brain of Fischer rat. (August 2015) - Desmarais, Guillaume; Charest, Gabriel; Fortin, David; Bujold, Rachel; Mathieu, David; Paquette, Benoit
Abstract Purpose: Radiation induces a neuro-inflammation that is characterized by the expression of genes known to increase the invasion of cancer cells. In Fischer rats, brain irradiation increases the infiltration of cancer cells and reduced the median survival of the animals. In this study, we have determined whether these adverse effects of radiation can be prevented with the cyclooxygenase-2 (COX-2) inhibitor meloxicam. Materials and methods: Brain of Fischer rats treated or not with meloxicam were irradiated (15 Gy) and then implanted with the F98 glioma cells. The median survival of the animals, the infiltration of F98 cells, and the expression of inflammatory cytokines and pro-migration molecules were measured. Results: Meloxicam reduced by 75% the production of prostaglandin E2 (bioproduct of COX-2) in irradiated brains validating its anti-inflammatory effect. Median survival was increased to control levels by the treatment of meloxicam following brain irradiation. This protective effect was associated with a reduction of the infiltration of F98 cells in the brain, a complete inhibition of radiation-enhancement of matrix metalloproteinase-2, and a significant reduction of tumor necrosis factor α (TNF-α) and tumor growth factor β1 (TGF-β1) expression. Using invasion chambers, interleukin-1β (IL-1β) stimulated by 5-fold the invasiveness of F98 cells, but this stimulation was completely inhibited by meloxicam. This suggests that a cooperation between IL-1β and COX-2 are involved in radiation-enhancement of F98 cell invasion. Conclusions: Our results indicate the importance of reducing the inflammatory response of normal brain tissue following irradiation in an effort to extend median survival in F98 tumor-bearing rats.